Evaluation of the Zone of Keratinized Tissue Using Exposed Acellular Dermal Matrix Over Tooth Extraction Sites: A Randomized Controlled Clinical Trial. Issue 2 (April 2015) - Ribeiro, Sergio; Ferreira, Vinícius; Stutz, Bianca; Casado, Priscila; Rodrigues, Diogo; Barboza, Eliane Porto
Abstract : Background: The presence of an adequate zone of keratinized tissue has been associated with implant health. This study evaluated the zone of keratinized tissue using exposed acellular dermal matrix (ADM) over extraction sites. Material and Methods: Fifteen sites received ADM, and fifteen control sites received no biomaterial. All sites were sutured with no attempt to achieve primary closure. Initial measurements of buccal and lingual keratinized tissue were taken from the mucogingival line (MGL) to the most coronal gingival margins. Final measurements were taken from the buccal MGL to the lingual MGL 90 days after surgery. Gingival biopsies were taken before implant placement. Results: Test and control groups exhibited a mean value of 4.40 ± 1.45 mm and 1.40 ± 1.40 mm, respectively. The newly formed tissue revealed similar histological aspect of normal keratinized tissue. Conclusion: Exposed ADM used over tooth extraction sockets can predictably be used to increase the zone of keratinized tissue.